2019
DOI: 10.3390/en12030368
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Transformer Insulating Fluids Using Membrane Separation Technology

Abstract: Oxidation of oil/paper insulation initiates premature aging and introduces carboxylic acids with eventual increase in oil acidity, which hampers the properties of the oil. In this paper, a membrane separation technology-based purification process for aged insulation oil has been evaluated and reported. The intent of the present study is to eliminate carboxylic acids, dissolved decay contents and other colloidal contamination present in aged oil and enhance the useful life of oil. The potential of the membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 24 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…This process is based on the removal of acidic elements, water and aging by-products in the oil using adsorption processes with activated bentonite as adsorbent. Figure 3 shows the adsorption processes, which include drying, filtering, sedimentation, and removing impurities [27,28]. The regeneration treatment is conducted in accordance with IEC 60422 Standard [29].…”
Section: Experiments Preparationmentioning
confidence: 99%
“…This process is based on the removal of acidic elements, water and aging by-products in the oil using adsorption processes with activated bentonite as adsorbent. Figure 3 shows the adsorption processes, which include drying, filtering, sedimentation, and removing impurities [27,28]. The regeneration treatment is conducted in accordance with IEC 60422 Standard [29].…”
Section: Experiments Preparationmentioning
confidence: 99%
“…Abdi et al [16] have conducted experiments to measure and correlate the effect of water content on the electrical properties of mineral oil and observed that after treatment, the breakdown voltage is increased as water content decreases. Safiddin et al [17] have taken the used transformer oil and with the help of the membrane separation technology process its life is enhanced by eliminating carboxylic acids.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Subsequently, these aging products will continue to accelerate the aging process. Instead of replacing insulating oil, the regeneration of insulating oil is a promising method that prolongs the transformer life and reduces carbon emissions [13][14][15].…”
Section: Introductionmentioning
confidence: 99%